The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1115/1.4023687
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Steam Reforming of Glycerol Over Cerium and Palladium-Based Catalysts for Hydrogen Production

Abstract: In this work, catalytic steam reforming of glycerol for hydrogen production was performed over Ce/Al2O3 and Pd/Al2O3 catalysts prepared via the impregnation method. The catalysts were characterized by scanning electron microscopy (SEM-EDX), transmission electron microscopy (TEM), BET surface area, and X-ray diffraction (XRD). Two sets of catalytic reactions were conducted, one comparing 1% Pd/Al2O3 to 1% Ce/Al2O3 and the second comparing 1% Ce/Al2O3 loading to 10% Ce/Al2O3 loading. All catalytic reactions were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…Catalysts containing group 8-10 metals such as Ni [7][8][9][10][11][12], Co [13][14][15][16], Pt [17][18][19][20][21], Ru [22][23][24], Rh [25], Pd [26] or Ir [27] on different oxides have been largely investigated as active catalysts for glycerol steam reforming. Ni-supported is one of the most promising active metals for such an application because of its high activity, low cost and wide availability.…”
Section: Introductionmentioning
confidence: 99%
“…Catalysts containing group 8-10 metals such as Ni [7][8][9][10][11][12], Co [13][14][15][16], Pt [17][18][19][20][21], Ru [22][23][24], Rh [25], Pd [26] or Ir [27] on different oxides have been largely investigated as active catalysts for glycerol steam reforming. Ni-supported is one of the most promising active metals for such an application because of its high activity, low cost and wide availability.…”
Section: Introductionmentioning
confidence: 99%
“…Ebshish et al [133] compared the catalytic performance of 1 wt.% Ce/Al2O3 and 1 wt.% Pd/Al2O3 catalysts, as well as the performance of 1 wt.% Ce/Al2O3 and 10 wt.% Ce/Al2O3. The authors observed that the 1 wt.% palladium catalyst supported on alumina presented better glycerol conversion to gaseous products as well as better H2 yield than both 1 wt.% Ce/Al2O3 and 10 wt.% Ce/Al2O3 catalysts.…”
Section: Other Noble Metal-based Catalystsmentioning
confidence: 99%
“…Moreover, because previous data were obtained with different catalyst systems and under different operating conditions, comparing catalysts prepared by different synthetic methods is difficult and inexact. The present work compares a group of NÍ/AI2O3 catalysts with various Ni loadings (6,8,10,12, and 20 wt. %) prepared by precipitation and impregnation procedures under the same set of catalyst and reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Several common routes are available for hydrogen production, including electrolysis and photolysis of water [1], extraction from biomass [2,3], steam reforming of hydrocarbons [4][5][6][7][8][9][10], and solar energy [11]. The hydrogen source ernployed depends largely on the geographical location of its demand.…”
Section: Introductionmentioning
confidence: 99%